The Influence of Employee Competencies on Increasing Women's Empowerment Through Programs Training at the Empowerment Office Women, Child Protection and Community (Dp3am) Binjai City - Lailan Azizah; Muhammad Isa Indrawan (International Journal of Society and Law, 2024)
Employee knowledge or competence will increase employee motivation in participating in training and employee performance. The purpose of this study is to find out and analyze the influence of Competence on Performance mediated by Training at the Office of Women's Empowerment, Child Protection and Community Protection (DP3AM) Binjai City. This research was conducted with a causal associative quantitative approach. The sample used was all employees with a total of 61 people. The results of data analysis using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) showed that Competence had a significant influence on employee performance (T-statistic 2,567 > 1.96; P-value 0.011 < 0.05), which indicates that improving Competency directly improves employee performance. Competence also had a positive and significant effect on Training (T-statistic 9.042 > 1.96; P-value 0.000 < 0.05), indicating that the improvement of Competency significantly increases employee training. Furthermore, training had a positive and significant effect on Performance (T-statistic 6,091 > 1.96; P-value 0.000 < 0.05), which means that the increase in Training significantly improves Performance. Indirect influence analysis showed that Training was able to intervene in the influence between Competence and Performance (T-statistic 5.974 > 1.96; P-value 0.000 < 0.05). These findings provide insight that Training plays a significant mediator role in the relationship between Competency and Performance, emphasizing the importance of Training in improving employee Performance.